Survival Analysis of Corneal Densitometry After Collagen Cross-Linking for Progressive Keratoconus. Issue 11 (November 2018) - Chan, Tommy C. Y.; Chan, Jason C. K.; Wang, Yu Meng; Rapuano, Christopher J.
Abstract : Purpose: To evaluate the history of densitometric data in patients with keratoconus undergoing corneal cross-linking. Methods: Twenty-two eyes of 22 patients with keratoconus were included. Corneal tomography and densitometry measurements were performed before and after accelerated corneal cross-linking. The duration of corneal haze was defined as the time between cross-linking and densitometry measurements returning to the preoperative value. Survival analysis of corneal haze after cross-linking was performed. Preoperative and postoperative corneal densitometry, maximum keratometry (Kmax), and central corneal thickness were compared. Results: The duration of corneal haze was 18.2 ± 3.8 months at the first zone of 0 to 2 mm and 10.9 ± 2.5 months at the second zone of 2 to 6 mm. There was no change in Kmax between the preoperative period and the time at which corneal haze resolved ( P = 0.394 at the first zone; P = 0.658 at the second zone). Compared with the measurement taken at resolution of corneal haze, Kmax at 1 year after haze resolution was lower (62.0 ± 9.9 D to 61.2 ± 9.9 D, P = 0.008 at the first zone; 63.6 ± 10.9 D to 62.5 ± 10.1 D, P = 0.016 at the second zone). There was a decrease of central corneal thickness between the preoperative period and the time at which corneal haze resolved (470.8 ± 34.1 μm to 464.8 ± 34.5 μm, P = 0.047 at the first zone; 465.0 ± 35.3 μm to 454.7 ± 37.2 μm, P = 0.001 at the second zone), but it remained unchanged after haze resolution ( P = 0.146 at the first zone; P = 0.067 at the second zone). Conclusions: Corneal cross-linking halted keratoconus progression when detectable haze was present. There was continuous corneal flattening measured at 1 year after haze resolution. Thinning of the cornea was seen only when haze was detectable after cross-linking.